2017
DOI: 10.3415/vcot-16-05-0075
|View full text |Cite
|
Sign up to set email alerts
|

The effect of limb amputation on standing weight distribution in the remaining three limbs in dogs

Abstract: Despite the fact that limb amputation is a commonly performed procedure in veterinary medicine, quantitative data regarding outcomes are lacking. The intention of this study was to evaluate the effect of limb amputation on weight distribution to the remaining three limbs at a stance in dogs. Ten dogs with a prior forelimb amputation and ten dogs with a prior hindlimb amputation; all of which had no history of orthopaedic or neural disease in the remaining three limbs were included in the study. Standing weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…The main spatial differences between pre‐ and post‐amputation periods for the male Iberian lynx are shown in both home‐range estimates and daily distances, suggesting decreased mobility may be due to the missing forelimb. After forelimb amputation, domestic carnivores face many difficulties in returning to normal behavior since they place more than 60% of their weight on their forelimbs (Cole & Millis, 2017). However, weight recorded at necropsy suggested that the individual adapted well to the new environment where released and was able to hunt wild prey once the supplemental feeding station was not in use.…”
Section: Discussionmentioning
confidence: 99%
“…The main spatial differences between pre‐ and post‐amputation periods for the male Iberian lynx are shown in both home‐range estimates and daily distances, suggesting decreased mobility may be due to the missing forelimb. After forelimb amputation, domestic carnivores face many difficulties in returning to normal behavior since they place more than 60% of their weight on their forelimbs (Cole & Millis, 2017). However, weight recorded at necropsy suggested that the individual adapted well to the new environment where released and was able to hunt wild prey once the supplemental feeding station was not in use.…”
Section: Discussionmentioning
confidence: 99%
“…However, the gait changes drastically with amputation. Although hindlimb amputation has been suggested to have a smaller effect on the unaffected limb than forelimb amputation ( 16 ), changes in gait and weight-bearing capacity of the forelimb, especially the contralateral forelimb; increase in weight-bearing capacity of the contralateral hindlimb; increase in lateral flexion of the spine; and extension of the lumbosacral joint have been observed after hindlimb amputation ( 16 18 ). In the current case, cranial cruciate ligament rupture of the right stifle joint was suspected, and degenerative lumbosacral stenosis was also present.…”
Section: Discussionmentioning
confidence: 99%
“…1,4,8 Since the gravity center in quadrupeds is located in the thoracic region, hindlimb amputation provides better gait than forelimb amputation. 3 Despite this, weight distribution to the remaining limbs has been evaluated most frequently by using a force platform, 9,10 commercial posture analyzer, 11 or force platform and kinematics. 12,13 Kinetic and temporospatial information can also be obtained by using a pressure-sensing walkway, which has already been standardized using healthy dogs.…”
Section: Introductionmentioning
confidence: 99%